The Effect of Gender Diversity on the Quality of Accruals in Financial Reports (Empirical Study of Manufacturing Companies on the IDX) - Auli, Figa; Natalis, Christian (GREENOMIKA, 2024)
The research was conducted with the aim of analyzing the influence of female board of commissioners, female finance directors and CFO variability on the quality of accruals in manufacturing companies on the IDX for the 2018-2022 period. This research used 195 companies as samples using multiple linear regression analysis techniques. The research results show that female board of commissioners and CFO variability have a significant effect on accrual quality, while female financial directors do not have a significant effect on accrual quality.